The Effects of Brand Equity on The Intention to Purchase the Products of Beadzyful - Fauzy, Aulia Shabrina; Susilowati, Christin (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to examine the effect of brand equity on purchase intention of Beadzyful products, focusing on the dimensions of brand awareness, perceived quality, and brand association. Design/methodology/approach – This study employs an explanatory research design using a quantitative approach to analyze the relationships between brand equity variables and purchase intention. Data were collected from 152 respondents using a non-probability sampling method with purposive sampling technique. The respondents completed a Likert-scale questionnaire, and the data were analyzed using IBM SPSS Statistics 26. Findings – The results indicate that brand awareness, perceived quality, and brand association each have a positive influence on purchase intention. These findings suggest that stronger brand recognition, higher perceived product quality, and favorable brand associations contribute to increased consumer intention to purchase Beadzyful products. Originality/value – This study contributes to brand equity literature by providing empirical evidence of how its key dimensions collectively influence purchase intention in the context of a small creative business. The findings offer practical implications for entrepreneurs in strengthening brand equity to enhance consumer buying interest.